Understanding The Link Between Chronic Inflammation And Diabetes Complications: A Systematic Review. (The Review of Diabetic Studies, 2025)
Background:Chronic inflammation has emerged as a central driver of diabetic complications, influencing microvascular (retinopathy, nephropathy, neuropathy) and macrovascular outcomes (atherosclerosis, cardiovascular disease). The interplay between metabolic stress and inflammatory signaling underlies tissue damage, endothelial dysfunction, and impaired repair mechanisms.Objective:This systematic review aimed to synthesize empirical evidence on the role of inflammatory biomarkers in the development and progression of diabetic complications.Methods:Following PRISMA 2020 guidelines, twelve peer-reviewed studies published between 2009 and 2025 were analyzed. Eligible studies included human participants with diabetes mellitus, reporting inflammatory biomarkers such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), C-reactive protein (CRP), serum amyloid A (SAA), monocyte chemoattractant protein-1 (MCP-1), and fibrinogen. Data were narratively synthesized due to heterogeneity in study designs and outcomes.Results:Elevated IL-6, TNF-α, CRP, MCP-1, and SAA were consistently linked to increased risks of diabetic nephropathy, retinopathy, neuropathy, and cardiovascular events. Genetic factors, such as the IL-6 −174GG genotype, showed protective effects against microvascular complications. Fibrinogen levels were associated with both macro- and microvascular pathology, reinforcing its predictive clinical utility.Conclusion:Inflammation is a unifying mechanism across diabetic complications, driven by metabolic and vascular stress. Biomarkers such as IL-6, CRP, and SAA hold diagnostic and prognostic potential, suggesting that anti-inflammatory strategies could enhance long-term management of diabetes-related vascular and neural injury.